KELAINAN PERKEMBANGAN KRANIOFACIAL FETUS MENCIT (Mus musculus L.) Strain DDW SETELAH PEMBERIAN EKSTRAK N-HEKSAN BUAH ANDALIMAN (Zanthoxylum acanthopodium DC.) - Mai Sarah; Emita Sabri; Salomo Hutahaean (Saintia Biologi, 2012)
The purpose of this study is to investigate the effect of n-hexane extract of andaliman (Zanthoxylum acanthopodium DC.) fruit on craniofacial development of DDW Mice (Mus musculus L.). Experiment was carried out using Completely Randomized Design (CRD) with 5 treatments and 6 replicates. Treatments consist of a blank control, vehicle control (1% CMC) and 3 concentrations of andaliman extract (2%, 4% and 6%). All treatments were administered by oral gavage (0.1 ml/10 g bw) once daily from day 0 to day 10 of gestation. N-hexane extract of andaliman fruit induced developmental abnormalities in craniofacial structures i.e. increased the incidence of microphthalmia (P <0.05), and hydrocephalus (P <0.05). In conclusion, we suggested that andaliman fruit may have fetotoxic effects. Keyword: andaliman (Zanthoxylum acanthopodium DC.), micropthalmia, hydrocephalus